The perceived impression of public on genetic engineering (Northern International Medical College Journal, 2015)
Genetic engineering (GE) - also known as genetic modification (GM), is the direct manipulation of an organism's genome using biotechnology. The field of genetic engineering deals with different kinds of alterations done on plants, animals and microorganisms and it has many applications in different sectors such as medicine, research, industry and agriculture. As GM plays an important role on food and agriculture, treatment of hereditary diseases, waste decomposition - all of which affects our lives, it concerns the geneticists and the general people alike.Objectives: The perceived impression of the mass population on Genetic engineering and analyzing how much it is accepted in todays society.Methodology: This descriptive cross sectional study was conducted from July to December 2013. Structured questionnaire was used to collect data from the concerned public around the world by using the site http://kwiksurveys.com/. [Link to this survey Results: Globally 67 people took the survey through web site and all of the participants were above 18 years of age and consisted of people who had little (53.73%) or no knowledge on GE (2.99%) and also people who were aware (31.34%) or had a deep knowledge (11.94%) of it. In this study 32.35% of people found the modification of genes Unethical but necessary and 30.88% of people found it Ethical and very useful. This showed that the majority of the people had accepted GE. When used for a good cause GE is morally acceptable to people (73.13%)Conclusion: This research has provided us a brief idea about the mental mental attitude or psychology of the respondents regarding the acceptance of GE in the society. This study showed that majority of the people belief GE will be beneficial some are still against it.Northern International Medical College Journal Vol.6(1) 2014: 32-35